Low temperature magnetic and transport properties of LSMO-PZT nanocomposites - Dwivedi G.D.; Kumar M.; Shahi P.; Barman A.; Chatterjee S.; Ghosh A.K. (My University, 2025)
Nanocomposites of La0.7Sr0.3MnO3-PbZr0.52Ti0.48O3 (LSMO-PZT) with varying PZT content have been synthesized by sol-gel method. XRD, HRTEM, SEM and EDX studies confirm the coexistence of both components (viz. LSMO and PZT) in the composites and reveal that the PZT nanoparticles occupy the surface and the grain boundaries (GBs). The M-H measurement of LSMO-PZT composites exhibits a weak ferromagnetic nature with low coercivities of 0.0123 T and 0.0142 T at 300 K and 80 K, respectively, and the highest magnetic moment (nB) achieved is 2.069 μB at 80 K for x = 0.01. The M-T studies confirm that the transition temperature (Tc) ≈ 360 K and the maximum entropy changes (ΔSm) are 0.40, 0.35 and 0.25 mJ Kg-1 K-1 at the magnetic field Hmax = 100 Oe for x = 0.01, 0.02 and 0.05, respectively. The average particle size of LSMO, PZT, and LSMO-PZT nanocomposites range between 24-30 nm, as confirmed from XRD, TEM, and magnetic measurements. Electrical resistivity studies show that the insulator-metal transition temperature (TIM) decreases rapidly with addition of a small amount of PZT and then remains almost constant with a higher concentration of PZT. The conduction in the insulator region is governed by tunneling between magnetic phases and in the metallic region the conduction shows non-Fermi liquid behavior. The resistivity increases with increasing PZT concentration. The energy barriers and scatterings are responsible for the increase in higher resistivity observed. The magneto-resistance (%MR) has been found to decrease with decreasing temperature. Variation in the MR at low temperature in LSMO-the PZT nanocomposite is due to the effect of the large spin polarization and pinning of domain walls at the GBs. © The Royal Society of Chemistry 2015.